Water erosion hazards Bshadr region in Sulaymaniyah Governorate - Al-Shammari, Muhammad Hisham Abdul Rahman Mohi; Al-jaf, Jwan sameen Ahmed (Al-Adab Journal, 2021)
Water erosion is one of the most important geomorphological processes that constantly change the shape of the Earth’s surface and its features, as its intensity varies depending on the causative factors, the most important of which are the climate, terrain and the nature of the geological formations that were addressed to the study area and their role as causative factors in showing the hazards to the area. Its intensity is according to the Bergsma system, and it was documented by a detailed map and categorized into ranges that showed five types of erosion, namely, the medium erosion range with an area of ​​(6.46 km2), the high erosion range with an area of ​​(124.71 km2), and the very high erosion range with an area of ​​(858.96 km). km2) which is the highest range of erosion in the region, and the range of severe erosion with an area of ​​(329.33 km2), and finally the range of very severe erosion, as the area of ​​this range reached (46.17 km2).